Integration of Character Values in Independent Curriculum Learning at SDN 2 Selat Penuguan - Resnita Resnita; Syarwani Ahmad; Destiniar Destiniar (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the Integration of Character Values in the Management of Independent Curriculum-Based Learning in State Elementary School 2, Selat Penuguan District, Banyuasin Regency. Data collection tools use interview methods, documentation, observation and literature review. Data analysis uses descriptive qualitative analysis with research stages that refer to the theory of Miles and Huberman, namely collecting data, data reduction, data presentation, drawing conclusions. The results of the study stated that the integration of character values in learning based on the Independent Curriculum at SD Negeri 2, Selat Penuguan District has been running well through 3 stages, namely 1) integration of character values into learning planning based on the Independent Curriculum as an effort to strengthen the character of students at SD Negeri 2, Selat Penuguan District; 2) integration of character values into the implementation of learning as an effort to strengthen the character of students at SD Negeri 2, Selat Penuguan District; 3) integration of character values into learning evaluations. Integrated learning planning with character values at SD Negeri 2, Selat Penuguan District The character values instilled at SD Negeri 2, Selat Penuguan District include (1) faith, devotion to God Almighty, and noble character; (2) independence; (3) mutual cooperation; (4) global diversity; (5) critical reasoning; and (6) creative.